Development and in vivo assessment of a novel MRI‐compatible headframe system for the ovine animal model. Issue 4 (3rd May 2021) - Trovatelli, Marco; Brizzola, Stefano; Zani, Davide Danilo; Castellano, Antonella; Mangili, Paola; Riva, Marco; Woolley, Max; Johnson, Dave; Rodriguez y Baena, Ferdinando; Bello, Lorenzo; Falini, Andrea; Secoli, Riccardo
Abstract: Background: The brain of sheep has primarily been used in neuroscience as an animal model because of its similarity to the human brain, in particular if compared to other models such as the lissencephalic rodent brain. Their brain size also makes sheep an ideal model for the development of neurosurgical techniques using conventional clinical CT/MRI scanners and stereotactic systems for neurosurgery. Methods: In this study, we present the design and validation of a new CT/MRI compatible head frame for the ovine model and software, with its assessment under two real clinical scenarios. Results: Ex‐vivo and in vivo trial results report an average linear displacement of the ovine head frame during conventional surgical procedures of 0.81 mm for ex‐vivo trials and 0.68 mm for in vivo tests, respectively. Conclusions: These trial results demonstrate the robustness of the head frame system and its suitability to be employed within a real clinical setting.